Study guides

Q: 8x-9 equals 11x plus 12

Write your answer...

Submit

Related questions

x=12

It is a linear equation in a single variable, x.

8x - 5 + 3x + 17 = 155% 11x + 12 = 1.55 11x = 1.55 - 12 = -10.45 x = - (10.45/11) = - 0.95

11x + 8 = 8x + 20 3x + 8 = 20 3x = 12 x = 4

11x+9=7x+21 11x-7x=4 4x+9=21 21-9=12 4x=12 12 divided by 4= 3 x=3

6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1

11 times 12 = 132

2x2 + 11x + 12 = 2x2 + 3x + 8x + 12 = x*(2x + 3) + 4*(2x + 3) = (2x + 3)*(x + 4)

12x+15p-6p+11x = 12x+11x+15p-6p = (12+11)x+(15-6)p = 23x + 9p

Y=13/11x + 12/11

12x - 5 = 11x + 5(1) add 5 to both sides:12x - 5 + 5 = 11x + 5 + 512x = 11x + 10(2) next subtract 11x from both sides:12x - 11x = 11x - 11x + 10x = 10

8x9=72; 72-12=60; 60-8=52.

Assuming the question is written as: x2+11x-12 This would factor to: (x+12)(x-1)

it equals 72. just do 12 X 6

4x + 8 + 7x + 12 = 11x + 20

it equals 70

12+12

12 plus 9 equals 21.

9*12 = 108

yes. think of 6/12 plus 1/12. that is 7/12!

x2 -11x-12= (x-12)(x+1)

5 plus 25 equals 60. Need to solve for 5 plus 25 equals ?: 2 plus 10 equals 24 is equivalent to 2 × (1 plus 5) equals 2 × (12); and 3 plus 15 equals 36 is equivalent to 3 ×(1 plus 5) equals 3 × (12); thus 5 plus 25 equals ? is equivalent to 5 × (1 plus 5) equals 5 × (12); thus ? = 5 × 12 = 60.

12 + 10 + 11 equals 33

It is: 12 plus 22 = 34

12 + 12 + 12 + 191 = 227